The Embankment dam proceedings of the sixth conference of the British Dam Society held in Nottingham on 12-15 September 1990. (Thomas Telford, 1991)
Presenting a survey of embankment dams, this book provides information from many countries on research, environmental considerations, risks, hazards, and safety. It is useful for engineers involved in the planning, design, construction, or operation of water-retaining embankments and tailing dams.